Zróżnicowanie cen kontrolowanych i inflacji w Unii Europejskiej - Kołodziej, Joanna; Paluszak, Grzegorz (The Regulated Prices and Inflation Differentials in the European Union, 2006)
The prices and inflation differentials are a normal phenomenon in long-established monetary union like the United States. The improvements in both European and national competition policies may further reduce price differentials for tradable goods and inflation differentials. Inflation differentials can be an integral part of the adjustment mechanism resulting form the dispersion of economic developments across the European countries. Therefore inflation differentials are not only unavoidable, but also desirable. However in the European Union, prices are characterised by systematically longer adjustment process, on the account of greater rigidity in price-setting mechanism. Additionally, the European governments increase these rigidities, because of the large weight of the regulated prices in the CPI basket and the HICP basket, and generate significant and persistent inflation divergence. The main aim of this paper is to compare the level, change and dispersion of the regulated prices and weight of these chosen prices in the CPI basket and the HICP basket. This article also presents the main causes of the dispersion of the regulated prices and their influence on inflation differentials.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 137-152